Multiple intelligences, emotions and creativity in first-year spanish undergraduate students - Sospedra-Baeza, María Josefa (2022)
Introduction: This research points in the direction of the relevance and usefulness of designing and applying interventions focused on improving intelligence, giving priority to emotional and creative aspects, to promote optimal comprehensive performance in students. There is a pronounced need to develop competent people, both cognitively and socioemotionally, to function effectively in an ever-changing society. Objective: The purpose was to evaluate and compare the level of self-efficacy perceived by the participants with respect to their multiple intelligences, their emotional intelligence, their creativity and their academic performance. Method: The sample is made up of 435 first-year university students. The research design was cross-sectional predictive. Results: Relationships were found between the analyzed variables, as well as differences based on the sex of the participants. Regression analyzes show how linguistic and logicalmathematical intelligences are self-perceived predictors of students’ academic performance. Discussion: A positive relationship between the different social and emotional competencies is detected, as well as their importance for the optimal performance of the students.